Innovation of Moringa Leaves as Steamed Pudding Cake to Prevent Stunting in Children - Ratna Juwita; Norman Yoshi Haryono; Muh Ade Artasasta; Algafari Bakti Manggara; Septiani Dewi Hamni; Winda Yael Galingging; Hilda Ainun Nikmah; Fira Alisya Nur Azizah (Universitas Indraprasta PGRI, 2023)
Moringa leaves are a local plant that contains high nutrition, which contains vitamins A and C. In addition, Moringa leaves also contain iron, magnesium and various kinds of amino acids. The nutrients contained in Moringa leaves are needed by the body. Therefore, the community service team at the State University of Malang carried out community service activities in Wonorejo village by making steamed pudding cakes from Moringa leaves. Wonorejo village is a village with potential for Moringa leaves. This community service focuses on family welfare supervisors (PKK) who are the main key in managing family nutrition. PKK women from Wonorejo village were given an understanding of the nutritional content in Moringa leaves and were also given training in processing Moringa leaves into steamed pudding cakes which are popular with all groups. Based on the results of the questionnaire that was carried out during community service, it was shown that 100% of the training participants had not used Moringa leaves as steamed pudding cakes. In this training, it is hoped that the community will become more concerned about the problem of stunting in children and the use of Moringa leaf nutrition as a solution to prevent it.